The Expanding Role of Extracorporeal Membrane Oxygenation Retrieval Services in Australia. Issue 1 (January 2017) - Edelman, J. J. B.; Wilson, M. K.; Vallely, M. P.; Bannon, P. G.; McKay, G.; Robertson, S. J.; Hislop, R.; Wong, C.; Cartwright, B. L.; Forrest, P.; Torzillo, P. J.
Herein we detail the cases of three patients transferred on veno-arterial extracorporeal membrane oxygenation (VA ECMO) from a tertiary referral hospital to an ECMO centre. We highlight the benefits of such a transfer and offer this as a model of care for unwell patients likely to require a prolonged period of ECMO support.